The 55-kD tumor necrosis factor receptor on human keratinocytes is regulated by tumor necrosis factor-alpha and by ultraviolet B radiation. - Trefzer, U (1993)
In previous studies we showed that cultured human keratinocytes expressed the 55-kD TNF receptor (TNFR) and that its expression the important for TNF alpha-mediated upregulation of intercellular adhesion molecule-1 (ICAM-1) expression on keratinocytes. Because factors that either reduce or enhance TNFR expression are likely to have a major impact on the biological effects of TNF alpha on keratinocytes, these studies were conducted to determine the factors that regulate its expression on keratinocytes. Using reverse transcriptase polymerase chain reaction, human keratinocytes were shown to lack 75-kD TNFR expression, indicating that TNF responsiveness of human keratinocytes critically depended on regulation of 55-kD TNFR expression. Human keratinocyte 55-kD TNFR surface and mRNA expression was found to be regulated in vitro by recombinant human (rh) TNF alpha. Stimulation of keratinocytes with rhTNF alpha initially decreased, but later increased, 55-kD TNFR surface expression. This biphasic modulation of 55-kD TNFR surface expression was associated with concomitant changes in 55-kD TNFR mRNA expression. Ultraviolet B (UVB) radiation, a well-known inducer of synthesis and secretion of TNF alpha by human keratinocytes, was found to mimic TNF alpha-induced modulation of 55-kD TNFR surface and mRNA expression via a TNF alpha-mediated autocrine regulatory mechanism. Production of soluble 55-kD TNFR by human keratinocytes remained unaffected by TNF alpha stimulation or UVB irradiation. These studies provide clear evidence that membrane expression of the human 55-kD TNFR may be regulated in human keratinocytes by the ligand itself: TNF alpha. Since in previous studies UVB irradiation transiently inhibited TNF alpha-induced human keratinocyte ICAM-1 expression, it is proposed that UVB radiation-induced biphasic modulation of human keratinocyte 55-kD TNFR expression may affect the capacity of these cells to respond to TNF alpha.